Papillary thyroid carcinoma arising within a mature cystic teratoma of ovary: a rare case report (Journal of Patan Academy of Health Sciences, 2020)
Mature cystic teratoma is the most common ovarian germ cell tumor with a rare malignant conversion. We report a case of 36 years lady, with an incidental post-operative finding of papillary carcinoma of the thyroid in histopathology of the left ovarian dermoid cyst. Postoperatively she was evaluated for the presence of primary thyroid tumor with thyroid ultrasonography, thyroid function test, and anti-thyroglobulin antibody which revealed normal thyroid gland with euthyroid status and negative anti-thyroglobulin antibody, which had ruled out primary thyroid tumor. There are limited case reports on papillary thyroid carcinoma in a mature cystic teratoma in absence of a struma ovary and specific recommendations on the plan of its management are not available. This study aims to report a rare case of papillary thyroid carcinoma arising in a mature cystic teratoma of the ovary in absence of a struma ovary.